2019
DOI: 10.1175/jpo-d-19-0170.1
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian Measurement of Steep Directionally Spread Ocean Waves: Second-Order Motion of a Wave-Following Measurement Buoy

Abstract: The notion that wave-following buoys provide less accurate measurements of extreme waves than their Eulerian counterparts is a perception commonly held by oceanographers and engineers (Forristall 2000, J. Phys. Oceanogr., 30, 1931–1943, https://doi.org/10.1175/1520-0485(2000)030<1931:WCDOAS>2.0.CO;2 ). By performing a direct comparison between the two types of measurement under laboratory conditions, we examine one of the hypotheses underlying this perception and establish whether wave measurement buoys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Wave buoys are known to underestimate extreme crests through several mechanisms, such as lateral movements around the crest, being dragged through the crest, or linearization of the sea state due to their Lagrangian motion. Even though these effects were found to be of minor importance 40 , we cannot rule out that our conclusions are potentially biased by this. Therefore, our buoy data could underestimate the total number of rogue waves to some degree, and the influence of second-order effects on wave crests might be even higher if measured by a different sensor (this does not affect wave heights, though).…”
Section: Discussionmentioning
confidence: 65%
“…Wave buoys are known to underestimate extreme crests through several mechanisms, such as lateral movements around the crest, being dragged through the crest, or linearization of the sea state due to their Lagrangian motion. Even though these effects were found to be of minor importance 40 , we cannot rule out that our conclusions are potentially biased by this. Therefore, our buoy data could underestimate the total number of rogue waves to some degree, and the influence of second-order effects on wave crests might be even higher if measured by a different sensor (this does not affect wave heights, though).…”
Section: Discussionmentioning
confidence: 65%
“…In McAllister and van den Bremer (2019), it was shown that the mooring configuration used for the experiments analysed here had no observable effect on the vertical displacement η. However, lateral (x, y) buoy position, which Fig.…”
Section: Mooring Configurationmentioning
confidence: 87%
“…As only three quantities are used for directional estimates made using buoy measurements, bimodal directional distributions may present a challenge. Identifying crossing sea states is important, as they can be hazardous for seafaring vessels and potentially increase the likelihood of observing large wave crests (McAllister et al 2019).…”
Section: Crossing Sea Statesmentioning
confidence: 99%
“…No matter the source, wave measurements inevitably suffer from a number of uncertainties. Wave buoy measurements exhibit deviations from the actual sea state due to the buoy response (McAllister & van den Bremer 2019), while radar is limited by wave shadowing (Plant & Farquharson 2012) (the inability to observe in the radar shadow of a wave crest). While an accurate measurement of the sea-surface height at a single instant, like that furnished by the WASS (wave acquisition stereo system) of Fedele et al (2013), would be ideal, radar measurements are further impacted by the rotation time of the radar antennae (typically several seconds (Al-Ani et al 2020)).…”
Section: Introductionmentioning
confidence: 99%